Criminal Law Reform in Indonesia : The Perspective on Freedom of Expression and Opinion - Fadhil, Moh. (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2023)
This article aims to discuss several criminal acts in the Indonesian Criminal Code that directly correlate with the right to freedom of expression and opinion. The analysis of these crimes employs the perspective of international human rights norms to assess the extent to which the mission of criminal law reform has been implemented in the reformulation process. This research uses a normative legal approach with statutory and conceptual approaches. The results of this study reveal that several criminal acts raise concerns regarding democratization and decolonization missions. These acts include the crime of attacking the dignity of the President and Vice President, the crime of participating in demonstrations, the crime of defaming the government and public control, the crime of defamation, and the crime of spreading disinformation. Although the crime of blasphemy has undergone significant transformation, it still possesses punitive potential if not restricted to material offenses. Moreover, the criminal act of disinformation requires further harmonization with the ITE Law. The incompatibility with the above missions confirms that some of these offences are disproportionate and potentially threaten freedom of expression and opinion.